The influence of parental support, nutritional status, and motor ability on physical education learning outcomes - David Yuliawan; Wilda Welis; Syahrastani Syahrastani; Sefri Hardiansyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study aimed to determine the direct and indirect effects of parental support, nutritional status, and motor ability on learning outcomes in Physical Education, Sports, and Health among students at SDN 26 Air Tawar Timur, Padang City. This study employed a quantitative correlational design using path analysis. The sample consisted of 56 elementary school students selected through cluster random sampling. Data were collected using a parental support questionnaire, Body Mass Index measurements to assess nutritional status, a Motor Ability Test, and students’ semester report scores in Physical Education, Sports, and Health. Data analysis included validity, reliability, normality, homogeneity, linearity, and path analysis tests using SPSS version 31. The findings showed that parental support had a significant direct effect on learning outcomes in Physical Education, Sports, and Health (β = 0.277; p = 0.020; 7.7%). Nutritional status also had a significant direct effect (β = 0.150; p = 0.028; 2.3%), while motor ability showed the strongest direct effect (β = 0.372; p < 0.001; 13.8%). Furthermore, parental support indirectly affected learning outcomes through motor ability by 28.6%, whereas nutritional status contributed indirectly by 6.6%.